Polymer - nanoparticle assemblies for array based sensing - Creran, Brian; Bunz, Uwe H. F.; Rotello, Vincent M. (Current organic chemistry, 2015)
Sensing clinically relevant biomolecules is crucial for the detection and prevention of disease. Currently used detection methods tend to be expensive, time intensive, and specific for only one particular biomolecule of interest. Nanoparticle-based arrays using conjugated polymers have emerged as an analytical and potential clinical tool, allowing detection of a wide range of biomolecules using selective, not specific, sensor components. In this report, we highlight recent progress in nanoparticle - polymer sensor arrays in both the fundamental understanding of how the sensor arrays function as well as the detection of clinically relevant bacteria and cells.,
Gesehen am 15.12.2020